Appropriateness of Antibiotics Prescription for Conjunctivitis in Primary Health Care: A Literature Review: Oral Presentation - Observational Study - General practitioner - Belinda Liliana; Atrika Fitri Nur Cahyani; Azura Nabila Putri; Oriana; Mohammad Eko Prayogo (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Conjunctivitis is one of the most common diseases present in primary health care (PHC) settings. The most common causes of conjunctivitis are viral infections and allergies. Despite this, patients diagnosed with conjunctivitis are often given antibiotics as therapy. Therefore, this literature review will assess the appropriateness of antibiotics prescription for patients with conjunctivitis in PHC settings. Methods : The authors performed an electronic literature search on databases PubMed and Scopus for eligible articles, which showed antibiotic prescription for patients with conjunctivitis in PHC settings and published between 2012 and 2022, then further sorted based on the inclusion and exclusion criteria. Results : A total of 8 studies met the inclusion criteria. Five studies showed high rates of inappropriate antibiotic prescriptions for patients with conjunctivitis in PHC. Several factors that might cause inappropriate prescription include the difficulty in determining the exact etiology, the need to fulfill patients’ satisfaction, the amount of experience and training doctors have received, consultation’s duration, stigma, the socio-demographic factors of the patient, the availability of treatment guidelines, and the availability of drugs. Some of the consequences that are concerned include the rise of antimicrobial resistance, stigma revolving around the usage of antibiotics for every infectious disease, and economic burden. Delays in prescribing antibiotics and proper training for general practitioners can be a solution to reduce inappropriate prescribing of antibiotics. Conclusion : Prescribing antibiotics for patients with conjunctivitis in PHC settings is mostly inappropriate